2001
DOI: 10.3171/jns.2001.94.2.0270
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effects of gamma surgery in a model of chronic spontaneous limbic epilepsy in rats

Abstract: In the first experiment, single doses of 20 or 40 Gy (but not 10 Gy) reduced substantially, and in some cases eliminated, behaviorally and electrographically recognized seizures. Significant reductions in both the frequency and duration of spontaneous seizures were observed during a follow-up period of up to 10 months postradiation. Histological examination of the targeted region did not reveal signs of necrosis. These findings indicate that single-dose focal ionizing beam irradiation at subnecrotic dosages re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 42 publications
0
70
1
Order By: Relevance
“…Therefore, our data demonstrated a progression of ischemic vascular injury with subsequent necrosis, leading to increased vascular permeability, vasogenic edema within and around the radiosurgical target, and finally focal encephalomalacia. These findings are somewhat unexpected, since preclinical investigations with the use of rat models of limbic epilepsy demonstrate that seizure reduction is not associated with tissue necrosis or a concomitant loss of neurons, [30][31][32] though most animals achieved improvement rather than remission of seizures. On the other hand, in humans, seizure remission after RS of other epileptic lesions-hypothalamic hamartomas or vascular malformations-does not require radiologic changes consistent with radionecrosis.…”
Section: Fluid-attenuated Inversion Recovery Coronal (A-e) T1 Coronamentioning
confidence: 64%
“…Therefore, our data demonstrated a progression of ischemic vascular injury with subsequent necrosis, leading to increased vascular permeability, vasogenic edema within and around the radiosurgical target, and finally focal encephalomalacia. These findings are somewhat unexpected, since preclinical investigations with the use of rat models of limbic epilepsy demonstrate that seizure reduction is not associated with tissue necrosis or a concomitant loss of neurons, [30][31][32] though most animals achieved improvement rather than remission of seizures. On the other hand, in humans, seizure remission after RS of other epileptic lesions-hypothalamic hamartomas or vascular malformations-does not require radiologic changes consistent with radionecrosis.…”
Section: Fluid-attenuated Inversion Recovery Coronal (A-e) T1 Coronamentioning
confidence: 64%
“…The experimental evidence suggests that, in rats, it is possible to achieve seizure control with subnecrotic doses of radiation. In studies in which an initial dose of 20 Gy was used, seizure abolition was reported in over 50% of the treated animals, with increasing seizure control associated with higher doses [14][15][16][17][18][19]. Overall, these studies suggest that a dose between 20 and 60 Gy given to rats provide seizure amelioration without frank histological necrosis.…”
Section: Biological Effect Of Irradiation On Seizuresmentioning
confidence: 99%
“…When tumors or other brain pathologies are targeted by GKRS, inevitably some surrounding normal healthy cells are also irradiated in the dose falloff volume around the target. The most basic irradiated brain tissue experiments were conducted to correlated the position planning of high dose of radiation with a necrotic area into the rat brain visualized by pathological observation (Chen et al, 2001;Kamiryo et al, 1993;Regis et al, 1996;Rey et al, 1996;Tokumaru et al, 2005a) or by MRi . The evolution of the histological changes after GKRS were also monitored in function of time (1-60 days) for the targeted volume and surrounding brain tissue (2 mm) (Kondziolka et al, 1992a).…”
Section: Response Of Healthy Brain To Focused Radiationmentioning
confidence: 99%
“…Another epileptic rat model was developed by repetitive electrical stimulations of the hippocampus in rats. The ventral hippocampus was irradiated and it is reported that a single dose of 20 or 40 Gy, but not 10 Gy, reduced substantially or eliminated the behavioral and EEG recognized seizures (Chen et al, 2001). These models of epileptic rats have improved our understanding of the fundamental mechanisms in epilepsy treatment by GKRS.…”
Section: Focused Radiation For Epilepsy and Parkinson Diseasementioning
confidence: 99%
See 1 more Smart Citation